فاعلية الذات وعلاقتها بدافعية الإنجاز الرياضي ومستوى الطموح لدى لاعبي كرة القدم الأقل من 17 سنة دراسة ميدانية على لاعبي كرة القدم الأقل من 17 سنة لفرق ورقلة وتقرت التابعين للرابطة الجهوية -ورقلة- - كنيوة ميلود (My University, 2018)
The purpose of this study was to know the level of self-efficacy, to investigate self-efficacy, achievement motivation, and state anxiety of football players in different playing position and to reach of finding the relationship between self-efficacy, achievement motivation, and state anxiety of football players. The sample consisted of male amateur football players (N =61) between the age 16 and 19 years. General self-efficacy scale- Schwarzer (GSES), task and ego orientation in sport questionnaire (TEOSQ), Competitive State Anxiety Inventory-2 (CSAI-2) were used to collection data. Descriptive statistics, kruskal-wallis Test and spearman’s correlation analysis were used to calculate data. The results indicated that there was high self-efficacy among football players. No statistically significant difference in football players’ self-efficacies, achievement motivations and state anxieties according to their playing position. And there was positive and significant correlation between self-efficacy and task orientation and between self-efficacy and self-confidence.
Keywords: Self-efficacy; Achievement motivation; State anxiety; Football players.